ANALYSIS OF RAHN'S STRATEGY TO INCREASE PROFITABILITY AND COMPETITIVENESS AT KSPPS NURI - Fadlillah, Fadlillah; Kadir, Abdul; Ali, Badrut (LP2M IAI Al-Khairat Pamekasan, 2024)
This study aims to comprehensively analyze the marketing and financing strategy of the Rahn contract (pawn) as the main instrument in increasing the profitability and competitiveness of KSPPS NURI in the Islamic financial market. In the context of increasingly fierce competition in the Islamic finance industry, it is important for KSPPS to adopt effective strategies to maintain and improve its position in the market. Akad Rahn, as one of the leading products in sharia financing, offers great potential in creating a stable source of income while attracting consumer interest. This study uses a qualitative descriptive approach with a case study method at KSPPS NURI. Data was collected through in-depth interviews, observations, and document analysis related to the implementation of Rahn's marketing and financing strategies. The results of the study show that the structured marketing strategy and synergy with Rahn's financing significantly increase the profitability of KSPPS NURI. In addition, the effective implementation of the Rahn contract also contributes to increasing the competitiveness of cooperatives in the Islamic finance market. However, the study also found some challenges, such as the need for innovation in products and improved service quality to maintain the sustainability of competitive advantage. Therefore, a sustainable strategy is needed to ensure the growth and sustainability of KSPPS NURI in the future.